2001
DOI: 10.1161/01.atv.21.4.523
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sex Differences and Effects of Endothelial NO Synthase Deficiency in Responses of Carotid Arteries to Serotonin

Abstract: Abstract-We examined the hypothesis that contraction of the carotid arteries to serotonin is normally inhibited by endothelial NO synthase (eNOS) and is enhanced in mice lacking the gene for eNOS. Because the influence of eNOS may vary with the sex of the mouse, we also tested whether responses to serotonin were dependent on sex. We studied carotid arteries in vitro from littermate control (eNOS ϩ/ϩ ) mice, heterozygous (eNOS ϩ/Ϫ ) mice, and homozygous eNOS-deficient (eNOS Ϫ/Ϫ ) mice (male and female). Contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 48 publications
8
71
2
Order By: Relevance
“…We found previously that responses of carotid artery to acetylcholine, nitroprusside, and serotonin are altered in heterozygous eNOS-deficient mice, although to a lesser degree than in homozygous eNOS-deficient mice. 25,26 Based on this finding, we anticipated that some degree of cerebral arteriolar hypertrophy might develop in heterozygous, as well as homozygous, eNOS-deficient mice, although possibly to a lesser extent than in the homozygous group. Cross-sectional area of the vessel wall, however, was virtually the same in cerebral arterioles of heterozygous eNOS-deficient mice and wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found previously that responses of carotid artery to acetylcholine, nitroprusside, and serotonin are altered in heterozygous eNOS-deficient mice, although to a lesser degree than in homozygous eNOS-deficient mice. 25,26 Based on this finding, we anticipated that some degree of cerebral arteriolar hypertrophy might develop in heterozygous, as well as homozygous, eNOS-deficient mice, although possibly to a lesser extent than in the homozygous group. Cross-sectional area of the vessel wall, however, was virtually the same in cerebral arterioles of heterozygous eNOS-deficient mice and wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…We included the study of eNOS ϩ/Ϫ mice, because it has been observed previously that vascular responses to some stimuli are altered in eNOS ϩ/Ϫ mice. 25,26 In addition, experts in the field of genetics encourage the study of heterozygous deficient mice because, depending on the results, they may encourage the study of genetic polymorphisms in humans. 27 Genotyping of the animals was performed by Southern blotting or polymerase chain reaction from tail biopsy specimens as previously described.…”
Section: Enos-deficient Micementioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that relaxation of the carotid artery to ACh in nontransgenic mice is normally mediated by NO and is consistent with our previous findings in eNOS-deficient mice. 28 In vessels treated with ceramide (1 mol/L), relaxation in response to higher concentrations of ACh was inhibited by Ϸ25%. For example, relaxation to 100 mol/L ACh was 92Ϯ6% and 71Ϯ6% in vehicle-treated and ceramide-treated (1 mol/L) vessels, respectively ( Figure 3A).…”
Section: Ceramide Produces Endothelial Dysfunction In Nontransgenic Micementioning
confidence: 96%
“…Nuno et al33 and Lamping and Faraci34 previously revealed male hypersensitivity to serotonin but not thromboxane A 2 in mice. However, no sex difference to serotonin responses was observed in studies using porcine vessels 35, 36.…”
Section: Discussionmentioning
confidence: 99%